Lead and cadmium accumulation in nearby brick kiln agri-environmental ecosystems - Sikder, Abdul Halim Farhad; Molla, Md Delwar Hossain; Hossain, Md Faruque; Parveen, Zakia (Bangladesh Journal of Scientific Research, 2016)
Three different brick kilns from the same parent material, young Brahmaputra and Jamuna floodplain were selected to assess the lead and cadmium accumulation. Soils and plants from four points such as 250, 500, 1000 and 1500 m away from kilns were collected based on the predicted brick kilns emission distance. Lead (92 mg kg-1 to 214 mg kg-1) was found in the elevated levels near brick kiln soils. The alarming news is that plant uptake of Pb in the nearest areas of the brick kilns were significantly higher than the areas far from the brick production location and Pb ranges from 7 to 543 mg/kg. Results showed that both soils and plants from 500 m to 1000 m distance received maximum Pb. The amount of Pb significantly decreases with the increasing distance from the brick kilns. Cadmium varies within the permissible limit in both soils and plant. Bangladesh J. Sci. Res. 28(1): 51-59, June-2015